Polymer Electron Acceptors Based on Fluorinated Isoindigo Unit for Polymer Solar Cells1. Issue 5 (15th March 2018) - Miao, Junhui; Xu, Han; Meng, Bin; Liu, Jun; Wang, Lixiang
Abstract : A new kind of polymer electron acceptors based on fluorinated isoindigo (F‐IID) as the electron‐ deficient building block has been developed. The resulting polymers based on F‐IID show low‐lying LUMO/HOMO energy levels, high electron mobilities and broad absorption spectra, enabling applications as electron acceptors in polymer solar cells. Abstract: Most of efficient polymer electron acceptors for polymer solar cells (PSCs) are based on naphthalene diimide or perylene diimide as the electron deficient building block. In this paper, for the first time, we report polymer electron acceptors based on fluorinated isoindigo (F‐IID) as the electron deficient building block. We synthesized two polymer electron acceptors consisting of alternating F‐IID unit and thiophene/selenophen unit. They show low‐lying LUMO/HOMO energy levels of –3.69/–5.69 eV, high electron mobilities of 1.31×10 –5 cm 2 ·V –1 ·s –1 and broad absorption spectra with the optical bandgap of 1.61 eV. PSC devices using the two F‐IID‐based polymers as polymer electron acceptors show encouraging power conversion efficiencies (PCEs) of up to 1.50% with an open‐circuit voltage ( V OC ) of 0.97 V, a short‐circuit current density ( J SC ) of 2.91 mA·cm –2, and a fill factor (FF) of 53.2%. This work suggests a new kind of polymer electron acceptors based on F‐IID unit.